An advantage of serving left-handed in tennis - Pollard, G. (Medicine and Science in Tennis, 2008)
Several players have a `better` service to one court side (usually the second court for left-handed players) than to the other side. This paper investigates whether players benefit from having this characteristic, rather than serving equally well to both sides. If such players have the ability to lift their play when serving, does it make any difference whether they lift their play to the `stronger` or `weaker` side? Should any such lifting be done early in the game or reserved for more important points? These questions are considered in this paper, and the outcome(s) might be considered surprising. It would seem that coaches and players might learn from some understanding of these mathematical / probabilistic considerations, and even develop their game and tactics in a way related to the theory.